2018
DOI: 10.18203/2320-1770.ijrcog20182319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different techniques of uterine closure in caesarean section: Continuous single layer technique versus Babu and Magon technique

Abstract: Background: To compare size of the caesarean scar and residual myometrial thickness (RMT) between continuous single non-interlocking and Babu and Magon technique for uterine closure following primary elective caesarean section (CS).Methods: An observational prospective cohort study was conducted at 6 weeks and 4 months postpartum following primary elective CS. Group A included 25 patients who underwent continuous single layer technique and Group B included 25 patients who underwent Babu and Magon technique for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In line with our data, Vinayachandran et al reported that the duration of uterine closure by the Babu and Magon technique and blood loss were different from those associated with conventional closure, but the difference was not statistically significant. 25 As the main outcome of the present study, a niche was observed on TVU after 12-14 weeks in 37.5% of women. The rate of cesarean scar defects varies from 20% to 60% in the published literature.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In line with our data, Vinayachandran et al reported that the duration of uterine closure by the Babu and Magon technique and blood loss were different from those associated with conventional closure, but the difference was not statistically significant. 25 As the main outcome of the present study, a niche was observed on TVU after 12-14 weeks in 37.5% of women. The rate of cesarean scar defects varies from 20% to 60% in the published literature.…”
Section: Discussionsupporting
confidence: 49%
“…The difference between the present study and Vinayachandran and coworkers' report appears to be due to differences in the study population: in the latter investigation, the indication for CS was elective and all women underwent CS before the onset of active labor. 25 In contrast, we performed 59.7% of CS (71% by the Babu and Magon technique vs 51% in controls) in the active phase of labor. We observed a significant relationship between CS in the active phase and the development of a niche.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation